2017
DOI: 10.29252/nrip.hdq.3.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Research Paper: Knowledge and Attitudes of Students in Khalkhal Medical Sciences Faculty on Health Actions in Emergencies

Abstract: Background: Health measures in an emergency are one of the cases where damage caused by disasters can be reduced with proper implementation, and the health crisis can be controlled. This requires awareness and knowledge of health and rescue authorities, students, and even people in an emergency situation. Therefore, the purpose of this study was to investigate knowledge of students' and attitude in Khalkhal Medical School in the field of emergency health measures. Materials and Methods:This is a descriptive-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…In this regard, the written guidelines at schools on the training of individuals, especially children to get ready for emergencies can be used. Also, the staff who have been trained for first aid and resuscitation can be employed to raise the people's knowledge and attitude [16][17][18]. On the one hand, the findings of these studies showed that the research on crisis management at the Iranian schools was very poor and most of them emphasized that students, teachers, and principals should be trained for crisis management and confrontation with it.…”
Section: Mostafavi Darani and Colleaguesmentioning
confidence: 99%
“…In this regard, the written guidelines at schools on the training of individuals, especially children to get ready for emergencies can be used. Also, the staff who have been trained for first aid and resuscitation can be employed to raise the people's knowledge and attitude [16][17][18]. On the one hand, the findings of these studies showed that the research on crisis management at the Iranian schools was very poor and most of them emphasized that students, teachers, and principals should be trained for crisis management and confrontation with it.…”
Section: Mostafavi Darani and Colleaguesmentioning
confidence: 99%
“…Moreover, the approaches of the Emergency and Disasters Health Department changed toward climate change, topics of public health, environmental health issues due to the crisis, and the need to control these issues before the crisis conditions [24][25][26][27]. Social welfare departments also attempted to develop ecological well-being disciplines, as well as assessing the occupational conditions and welfare of labor children and their conditions.…”
Section: The Necessity Of Establishment Of Hse Major At the Universitmentioning
confidence: 99%
“…Students may develop a variety of parasitic, infectious diseases and diarrheal if the principles of environmental health and school safety are not followed [4]. Studies show that 59% of students are infected with intestinal parasites and 29.5% with monocytes.…”
Section: Introductionmentioning
confidence: 99%